Patients with Multimorbidity and Their Treatment Burden in Different Daily Life Domains: A Qualitative Study in Primary Care in the Netherlands and Belgium. Issue 1 (2018) - Van Merode, Tiny; Van De Ven, Karin; Van Den Akker, Marjan
Background: Physicians and other healthcare professionals involved in the care of patients with multimorbidity should consider the problems these patients experience in managing their own conditions. However, treatment burden from the patient's perspective has been poorly explored, even though this might hamper treatment adherence. Objective: The present study examined the experiences of patients with multimorbidity in primary care in the Netherlands and Belgium using semi-structured interviews, with special attention to the daily life domains of treatment burden. Design: Individual interviews gathering qualitative data to explore the treatment burden experienced by patients with multimorbidity in primary care. Twenty-two patients agreed to participate: seven men and fifteen women. The recorded interviews were transcribed verbatim and evaluated using thematic content analysis. Results: The patients reported numerous aspects of treatment burden they experienced in various domains of their daily lives. These topics were categorized into four daily life domains of burden: organization of care, medication, patient's role, and impact on daily life (including the involvement of caregivers). Conclusions: The findings indicate that primary care patients with multimorbidity report treatment burden in several domains of their daily lives, not restricted to medical issues, such as side effects of medication. Some issues, such as those related to organization of care, seem easily modifiable. Further research is required focusing on special factors of treatment burden as experienced by patients with multimorbidity, and the implications for treatment adherence, especially in European settings, as little information is currently available.